Simulation of GNSS Signal with Noise and Distance, Speed Probability Distribution Calculation - Barzdziukas, J. (Elektronika ir Elektrotechnika, 2012)
Calibration or verification of measurement equipment needs standard measurement which must have sufficient precision and accuracy. GNSS usually has variable precision and accuracy with each measurement. In this article signal generation directly in frequency-delay representation is presented which can be used for decomposition or multipath interference correction. Demodulated signal maximal value distributions for frequency and delay are found from signal and known noise. These distributions allow to calculate measurement uncertainties for each satellite separately. Ill. 9, bibl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1839